صفة التجدد والحياة للفقه الإسلامي: نظام مقاصد الشريعة المعاصر - Ghazna Nizami, Auliya; Prima Pratista, Farida (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2025)
Sometimes, it might be seen that the contents of Islamic jurisprudence is a set of laws or regulations, whether religious or social, that manage the matter of life and its source the Almighty, that does not accept change at all, if we try to change it, the attempt might be known as an attempt to make bid’ah in religon-which is forbidden in Islam-. Even atheists and extremists in religion have inferred it to justify all the radical behavior that has remained under the umbrella of religious jihad. Jasser also saw those conditions in a city-London- that has a high level of security and elements that guarantee security and make it its starting point to get rid of the symbol of atheism and extremism from religion, whatever the religion - especially the religion of Islam - because religion is in its nature spreading safety, not in the position of spreading fear to scare people then runaway from it. Jasser saw that the trait of “renewable” and “alive” is what was completely absent from religion - from the viewpoint of its adherents - and tried to find these traits of the religion itself, because he believed that religion is the solution and not a source of the problem. This research spoke about the foundations of Jasser’s academic and scientific endeavors to make religion go hand in hand, like the solution, with modernity and endless realities. And he invented that the religious system corresponding to modernity must possess the six factors, namely: the cognitive nature of systems, wholeness, openness, and the hierarchical structure of interrelated hierarchy and multi-dimensionality and the Purposefulness or Goal-oriented.